Báo cáo Tiếp thu, giải trình ý kiến thẩm định của Bộ Tư pháp đối với Dự án Luật Điện lực (sửa đổi) - Bộ Công thương (2024)
Toàn văn Báo cáo Tiếp thu, giải trình ý kiến thẩm định của Bộ Tư pháp đối với Dự án Luật Điện lực (sửa đổi).